Konflik Batin Tokoh Alena dalam Menghadapi Tekanan Sosial pada Novel Lilin Karya Saniyyah Putri S.S : Tinjauan Psikoanalisis Sigmund Freud - Latifatul Hasanah; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The phenomenon of social pressure experienced by individuals often triggers complex inner conflicts and affects their psychological stability. This study aims to describe the form of inner conflict of the character Alena in facing social pressure in the novel Lilin by Saniyyah Putri S.S. The data collection technique used was a literature study by reading, recording, and identifying data from the novel. The data analysis technique used was a qualitative descriptive analysis with Sigmund Freud's psychoanalytic approach, which includes the id, ego, and superego. The results of the analysis show that the character Alena experiences an inner conflict that is predominantly influenced by social pressure from the family and community environment, which is reflected through the tug-of-war between subconscious drives and the moral values she believes in. The conclusion of this study is that the inner conflict experienced by Alena is raised in the continuity between the id, ego, and superego, which strengthens the relevance of Freud's psychoanalytic theory in understanding the dynamics of the psyche of fictional characters